2019
DOI: 10.1108/itp-06-2018-0280
|View full text |Cite
|
Sign up to set email alerts
|

Crime and social media

Abstract: Purpose The purpose of this paper is to complement the scant macroeconomic literature on the development outcomes of social media by examining the relationship between Facebook penetration and violent crime levels in a cross-section of 148 countries for the year 2012. Design/methodology/approach The empirical evidence is based on ordinary least squares (OLS), Tobit and quantile regressions. In order to respond to policy concerns on the limited evidence on the consequences of social media in developing countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…Since the study relies on cross-sectional averaged data, Ordinary least square (OLS) is used for the study to follow the extant literature (Andrés, 2006;Kodila-Tedika & Asongu, 2015;Asongu et al, 2019). Following the study of Stoddard and Noy (2015), Dornean and Oanea (2015), equation 1expresses the relationship between FDI outflows and COVID-19 variables including control variables.…”
Section: Ordinary Least Squarementioning
confidence: 99%
See 2 more Smart Citations
“…Since the study relies on cross-sectional averaged data, Ordinary least square (OLS) is used for the study to follow the extant literature (Andrés, 2006;Kodila-Tedika & Asongu, 2015;Asongu et al, 2019). Following the study of Stoddard and Noy (2015), Dornean and Oanea (2015), equation 1expresses the relationship between FDI outflows and COVID-19 variables including control variables.…”
Section: Ordinary Least Squarementioning
confidence: 99%
“…For robustness check, we employ Quantile regression (QR) in order to mitigate the static assumption of conditional mean of the dependent variable under OLS technique. The QR enables us to estimate the parameter throughout the conditional distribution of the dependent variable (Koenker & Bassett, 1978;Asongu et al, 2019). Using this technique, we are able to estimate the lower, intermediate and higher level of FDI outflow.…”
Section: Quantile Regressionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Part of the reason for the potential exposure to cyber hate in Indonesia is that internet usage is dominated by communication activities via messages (24.7%) and social media (18.9%). Although more research is needed, there are indications that crime is relevant to social media (Asongu, Nwachukwu, Orim, & Pyke, 2019). Indeed, according to Wang, Yu, Liu, and Young (2019), the two can be linked by using social media as a tool for crime control.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship may be very complicated. Taking Facebook as an example, Asongu and his colleagues conducted research focusing on the correlation between Facebook penetration and crime rate [7]. It was found that the two factors are actually negatively correlated, which means a higher level of Facebook penetration is correlated with a lower level of violent crime.…”
Section: Influence Of Social Media On Criminal Behaviorsmentioning
confidence: 99%